Severe recurrent hypernatremia and probable lithium-associated nephrogenic diabetes insipidus following pancreatectomy in a patient with schizophrenia: a case report - Yanfei He; Liuyin Jin; Xiaolei Xu; Qing Xia (Frontiers in Medicine, 2026)
Background Nephrogenic diabetes insipidus (NDI) is characterized by impaired renal responsiveness to arginine vasopressin, causing defective urinary concentration and large volumes of dilute urine. Long-term lithium exposure is an important acquired cause. Perioperative fasting, restricted free-water intake, and ongoing fluid losses may unmask compensated lithium-associated urinary concentrating dysfunction and precipitate severe hypernatremia. Case presentation A 61-year-old man underwent laparoscopic resection of a pancreatic tail lesion. His history included schizophrenia, type 2 diabetes mellitus, impaired renal function, long-term lithium therapy, and preoperative polyuria, nocturia, and polydipsia. Preoperative serum sodium was 147.1 mmol/L, creatinine 174.4 μmol/L, and eGFR 35.6 mL/min. Postoperatively, restricted free-water intake was followed by progressive polyuria, persistent negative fluid balance, altered mental status, and worsening renal function. Urine output peaked at 7,900 mL/24 h and serum sodium at 165.5 mmol/L. Despite marked hypernatremia and hypertonicity, urine specific gravity remained ≤1.005. Serum lithium before discontinuation was 0.90 mmol/L. Based on long-term lithium exposure, preoperative symptoms, persistent polyuria, recurrent severe hypernatremia, and low urine specific gravity, probable lithium-associated NDI was considered. Because urine osmolality and a standardized desmopressin response test were unavailable, NDI could not be biochemically confirmed and central diabetes insipidus could not be definitively excluded. Hyperglycemia, gastrointestinal fluid losses, and renal dysfunction may also have contributed. Management and outcome Lithium was discontinued after psychiatric and multidisciplinary consultation, and hydrochlorothiazide was initiated. Treatment included gradual free-water replacement, intravenous fluid adjustment, sodium restriction, enteral free water administered separately from enteral nutrition, and close monitoring of serum sodium, potassium, renal function, urine output, glucose, and mental status. The retrospectively estimated free-water deficit was approximately 7.5 L. With combined management, serum sodium, urine output, and consciousness gradually improved. At 12 weeks, serum sodium was 142.3 mmol/L. At 13 months, urine specific gravity remained 1.004, although persistent NDI could not be confirmed. Conclusions In patients receiving long-term lithium, postoperative polyuria, recurrent hypernatremia, and low urine specific gravity should prompt consideration of lithium-associated urinary concentrating dysfunction while other causes of water loss are assessed. Careful perioperative medication review, sodium and fluid-balance monitoring, individualized fluid management, and multidisciplinary collaboration are essential.